Efektivitas Skabisida Ekstrak Daun Mimba (Azadirachta indica A. Juss) Terhadap Tungau Sarcoptes scabiei Secara In Vitro (In Vitro Test of Scabicide Effectiveness of Neem Leaves Extract (Azadirachta indica A. Juss) on Sarcoptes scabiei mite) - fikri ahadian (Universitas Sumatera Utara, 2012)
Abstract : Scabies is one of the decreasing factor on ruminants growth, especially in goat. The expensiveness and the difficulties to get the scabies medicines in the rural area becomes the major problem for the traditional goat breeder. This research using Neem leaves extract (Azadirachta indica A. Juss) was chosen as an alternative solutions for it. The experiment was conducted in Loka Penelitian Kambing Potong Sei Putih, Kecamatan Galang, from February to April 2012, using posttest only control group design. The exploratory test was done by applying five concentration of neem leaves extract (0%; 25%; 50%; 75%; and 100%) with four replications each. The full scale test was using six treatments (0%; 5%, 10%, 15%, 20%, and 25%) with four replications each. 10 Sarcoptes scabiei mites were used for each replications. Parameters measured are mite mortality number, rate of mite mortality number, and lethal concentration. The results showed there were increasing on mite mortality numbers in each treatment, where the LC50 value is 13,18%. The results indicated that Neem Leaves Extract is an effective scabicide for Sarcoptes scabiei mite In Vitro. Key words : Scabicide, Sarcoptes scabiei, Azadirachta indica A. Juss